Material management and the survival of block molding firms - Shodiya Olayinka Abideen (Economic Review: Journal of Economics and Business, 2024)
The purpose of this study is to examine the effect of material management on the survival of block molding firms in a selected Local Government Area of Ogun State, Nigeria. This study collected data from 100 block molding enterprises from a population of 229 registered businesses in the block molding industry through survey research. To collect data from the respondents, a structured questionnaire with a five-point Likert scale was used. Cronbach's Alpha was used to validate the reliability of the variables utilized in the study. The data was analyzed using descriptive statistics, and the responses were represented using a simple percentage technique. PLS-SEM was used to analyze inferential statistics. The result showed that the coefficient of material procurement (Ø = 0.114, t = 5.195, p = 0.05) was found to have a significant positive relationship with block-producing-business survival. It also showed that the coefficient of inventory control (Ø = 0.837, t = 5.514, p = 0.05) was found to have a significant positive relationship with block-producing-business survival. The results further showed that the coefficient of material management (Ø = 0.965, t = 4.838, p = 0.05) was found to have a significant positive relationship with block-producing-business survival. The study concluded that a cohesive material management strategy can strengthen longevity. It advocated, among other things, that block-producing enterprises implement an integrated approach that harmonizes material procurement and inventory control in order to capitalize on the synergistic benefits of material management. This entails creating complete material management plans that optimize the whole supply chain, from sourcing to storage and distribution.
Keywords: M30; 330; from sourcing to storage and distribution; optimize the whole supply chain